2012
DOI: 10.1016/j.microrel.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on the bulk discharge current of dielectric films of MEMS capacitive switches

Abstract: a b s t r a c tKelvin probe method has been directly applied to capacitive MEMS switches in order to investigate temperature activated mechanisms in PECVD Silicon Nitride (SiN x ) films. The bulk discharge current of MEMS capacitive switches has been determined for different charging and discharging temperatures, in the range of 300-400 K. The increase of discharging temperature leads to an increase of the magnitude of the bulk discharge current and the relaxation time of the discharging process is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…3b). These charging processes include the effect of charge trapping, hopping [18] and percolation and they will lead to a macroscopic behavior that obeys the stretched exponential law [14,15] with time constants of 48 s and 1005 s for the contacted and contactless charging respectively. The low value of charging time can be attributed to the large applied electric field and mainly to the short observation time window.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). These charging processes include the effect of charge trapping, hopping [18] and percolation and they will lead to a macroscopic behavior that obeys the stretched exponential law [14,15] with time constants of 48 s and 1005 s for the contacted and contactless charging respectively. The low value of charging time can be attributed to the large applied electric field and mainly to the short observation time window.…”
Section: Resultsmentioning
confidence: 99%
“…The bulk discharge current transient in a MEMS capacitive switch is determined using the device model proposed in [14,15], which includes a fixed non-flat metal plate of area A covered with a dielectric film of uniform thickness d e and dielectric constant e r .…”
Section: Kelvin Probe Methods In Memsmentioning
confidence: 99%
“…The dielectric charging was strongly affected by temperature and increased exponentially with temperature, especially with high temperature [ 70 ]. The increase of charging temperature assists the charge trapping and the increase of discharging temperature leads to an increase in the magnitude of the bulk discharge current [ 71 ]. Zhen et al [ 72 ] studied the impact of humidity on dielectric charging in RF MEMS capacitive switches and found that bulk charging dominated in dry air, but surface charging increased linearly with increasing humidity.…”
Section: The Research Status Of Mems Switches In Different Frequenmentioning
confidence: 99%
“… 10 6 V/cm) and trapped in defects, characterized by long trapping time constants [5]- [7]. The trapped charge gives rise to shift of pull-in and pull-out voltages and finally to device failure due to stiction [4], [8]. Another charging mechanism is the induced charging that under certain conditions that can be large enough to give rise to compensation [9], [10].…”
Section: Introductionmentioning
confidence: 99%